Learning the language of Scripture : Origen, wisdom, and the logic of interpretation - James, Mark Randall (Studies in systematic theology (Leiden, Netherlands), 2021)
"In Learning the Language of Scripture, Mark Randall James offers a new account of theological interpretation as a sapiential practice of learning the language of Scripture, drawing on recently discovered Homilies on the Psalms by the influential early theologian Origen of Alexandria (2nd-3rd c. C.E). Widely regarded as one of the most arbitrary interpreters, James shows that Origen's appearance of arbitrariness is a result of the modern tendency to neglect the role of wisdom in scriptural interpretation. James demonstrates that Origen offers a compelling model of a Christian pragmatism in which learning and correcting linguistic practice is a site of the transformative pedagogy of the divine Logos"--